2020
DOI: 10.1097/jom.0000000000002033
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte Beverage Intake to Promote Hydration and Maintain Kidney Function in Guatemalan Sugarcane Workers Laboring in Hot Conditions

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…However, since blood was drawn at the end of the workday and thus increased plasma volume from overhydration may be a concern as described above, we chose to use the lower, more conservative definition. Similiarly, it is possible that hematocrit values were reduced somewhat by high levels of free water intake among the workers as we have seen in another study in this population [34,65], although we did not measure fluid intake, serum osmolality or cross shift weight change as part of this study to be able to confirm this effect. Efforts by Pantaleon to promote consumption of electrolytes (5 L per day) in lieu of free water intake (now recommended ad libitum) among workers in recent years have lessened our concern about this issue.…”
Section: Limitations and Future Directionsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, since blood was drawn at the end of the workday and thus increased plasma volume from overhydration may be a concern as described above, we chose to use the lower, more conservative definition. Similiarly, it is possible that hematocrit values were reduced somewhat by high levels of free water intake among the workers as we have seen in another study in this population [34,65], although we did not measure fluid intake, serum osmolality or cross shift weight change as part of this study to be able to confirm this effect. Efforts by Pantaleon to promote consumption of electrolytes (5 L per day) in lieu of free water intake (now recommended ad libitum) among workers in recent years have lessened our concern about this issue.…”
Section: Limitations and Future Directionsmentioning
confidence: 76%
“…In brief, sugarcane cutters work a six-day workweek followed by one day off, working approximately eight hours per day with two hours of rest breaks including lunch. Sugarcane cutting in Latin America demands high levels of physical exertion in a hot, humid environment, and has been associated with a metabolic load of 261 W/m 2 (6.8 kcal/min) [30]; caloric and hydration demands are therefore comparable to those of endurance athletes [31][32][33][34].…”
Section: Methodsmentioning
confidence: 99%
“…7,9 In Guatemala, a study with 50 sugarcane workers compared the consumption of electrolyte solution at 2.5 L per day, 5 L per day, and 10 L per day. 6 While kidney function remained normal in the three groups, workers reported that 5 L was the best quantity to drink. 6 As of yet, there are no field-based US studies of electrolyte interventions to protect agricultural workers from dehydration and AKI.…”
mentioning
confidence: 87%
“…4,5 More recently, they have also been shown to be at risk of acute kidney injury (AKI) and chronic kidney disease of unknown etiology (CKDu). [4][5][6][7] Drinking enough water is an important factor in preventing HRI. 8 The National Institute for Occupational Health and Safety (NIOSH) recommends drinking 24 to 32 ounces (oz) (0.7 to 0.9 L) of water per hour when working in the heat to stay hydrated.…”
mentioning
confidence: 99%
“…Pantaleon and CHWE signed a memorandum of understanding with the main purpose of evaluating and improving the health, safety and well-being of Pantaleon’s diverse workforce using a TWH approach. As the collaboration evolved, CHWE researchers assisted the company with identifying priorities and in addressing several of them, such as Chronic Kidney Disease of unknown cause (CKDu), hearing conservation & noise mitigation in the sugar processing mills, worker nutrition, hydration, and injury and illness surveillance [ 32 , 33 , 34 , 35 , 36 , 37 ]. While progress was made in these specific areas, it was clear that the company could benefit from a comprehensive TWH needs assessment and leadership assessment to identify additional priorities for intervention.…”
Section: Case Study: a Model To Apply The Twh Approach To Latin Ammentioning
confidence: 99%